Implementation of Data Collection and Payment Control Systems Automatically Using Android -Based QR Code - Afifah Nur Fauziah; Abdul Rasyid; Rieke Adriati Wijayanti (Politeknik Negeri Malang, 2023)
The wider spread of the use of smartphones is also very helpful for UMKM not only in terms of marketing or sales, but daily operations. On the Senyum Manis cafe the owner of the business owner conducts data on stocks of goods, materials, and prices for drinks manually. When doing the process of collecting the goods manually there is an error in stock calculation so that it takes a long time to check the stock of the item. With this innovation using the application of QR Code which can be used as a label in every stock of goods and beverage materials. In this case the implementation of the RFID tag is also used to get the customer queue number. From this researcher the system is considered successful because the data input can appear in the application , QOS (Quality of Service) test results when uploading data get a 33K throughput value that belongs to the medium category, Packet Loss produces a value of 0.097% which is classified in a very good category, average delay produces a value of 87.4 s which is classified in a very good category . This aims to anticipate changes that will occur, the review is useful to see the condition of whether the system is in accordance with the needs of a sweet smile cafe and whether it is necessary to add or change the existing system in order to keep up with development technology.